Long term outcomes of patients with tuberculous meningitis: The impact of drug resistance. - Emily E Evans; Teona Avaliani; Mariam Gujabidze; Tinatin Bakuradze; Maia Kipiani; Shorena Sabanadze; Alison G C Smith; Zaza Avaliani; Jeffrey M Collins; Russell R Kempker (PLoS ONE)
Background Little is known about the impact of drug-resistance on clinical outcomes among patients with tuberculosis meningitis (TBM). Methods A retrospective cohort study among patients treated for TBM in Tbilisi, Georgia. We performed medical chart abstraction to collect patient data. Long-term vital status was assessed using the Georgia National Death Registry. We utilized a Cox proportional-hazards model to evaluate the association of drug-resistance and mortality. Results Among 343 TBM suspects, 237 had a presentation consistent with TBM. Drug resistance was suspected (n = 5) or confirmed (n = 31) in 36 patients including 30 with multidrug- or rifampin-resistance and 6 with isoniazid-resistance. Thirty-four patients had HIV. The median follow-up time was 1331 days (IQR, 852-1767). Overall, 73 of 237 (30%) people died with 50 deaths occurring during and 23 after treatment. The proportion of death was higher among patients with drug-resistant vs. drug-susceptible disease (67% vs. 24%, p<0.001) and with HIV versus no HIV (59% vs 27%, p<0.001). Mortality was significantly higher in patients with drug-resistant TBM after 90 days of treatment (aHR = 7.2, CI95% [3.6-14.3], p < 0.001). Conclusions Mortality was high among patients with drug-resistant TBM with many deaths occurring post treatment. More effective treatment options are urgently needed for drug-resistant TBM.